Low Temperatures in Gerontological Practice of Dentist - Kutsevlyak, V. F.; Bozhko, K. B.; Sirota, O. N. (Problems of Cryobiology and Cryomedicine, 2008)
In aged people with the damaged oral cavity membrane due to numerous background diseases the traditional treatment not always succeeds. On the results of experimental and clinical studies there was performed either cryosurgical treatment or hypothermia of pathological foci. The results of cryoregenerative therapy were positive for 97% of patients.